Residual Herbicides as Single and Sequential Treatments for Efficacy in Corn - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
This research investigated the use of sequential applications of residual herbicides for the weed-free period in corn. The objective of the study was to compare residual herbicides as either preemergence (PRE) alone or split applications (PRE followed by postemergence). All treatments controlled Palmer amaranth, common lambsquarters, Russian thistle, and green foxtail 90% or more, and kochia 95% or more. Johnsongrass control early in the season was 91% or more regardless of treatment. However, no herbicide controlled johnsongrass as much as 80% late in the year.
Keywords: Residual control; palmer amaranth; lambsquarters; thistle; foxtail; johnsongrass